1999
DOI: 10.1103/physrevb.60.3453
|View full text |Cite
|
Sign up to set email alerts
|

Excess spin and the dynamics of antiferromagnetic ferritin

Abstract: Temperature-dependent magnetization measurements on a series of synthetic ferritin proteins containing from 100 to 3000 Fe(III) ions are used to determine the uncompensated moment of these antiferromagnetic particles. The results are compared with recent theories of macroscopic quantum coherence which explicitly include the effect of this excess moment. The scaling of the excess moment with protein size is consistent with a simple model of finite size effects and sublattice noncompensation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
77
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 19 publications
12
77
0
2
Order By: Relevance
“…Although other explanations for the anomalous behavior of antiferromagnetic nanoparticles have been suggested [9,12,14,15], the experimental data and the fit, shown in Fig. 1, together with a number of similar experimental observations, give experimental evidence for a temperature dependent magnetic moment that is in accordance with the model for thermoinduced magnetization.…”
Section: -2supporting
confidence: 65%
See 4 more Smart Citations
“…Although other explanations for the anomalous behavior of antiferromagnetic nanoparticles have been suggested [9,12,14,15], the experimental data and the fit, shown in Fig. 1, together with a number of similar experimental observations, give experimental evidence for a temperature dependent magnetic moment that is in accordance with the model for thermoinduced magnetization.…”
Section: -2supporting
confidence: 65%
“…Still, the dependence of the magnetization on particle size and temperature has shown features that are not fully understood. Several studies have revealed that the temperature dependence is not in accordance with the Langevin behavior, i.e., the magnetization does not decrease with increasing temperature in the expected way [8][9][10][11][12][13][14][15]. These results have been observed in several synthetic samples, in the iron storage protein ferritin, and in ferrihydrite, which can be found in sediments in nature.…”
supporting
confidence: 49%
See 3 more Smart Citations